Enteral Delivery of Pravastatin Sodium Tablets: Effect of Compounding into a Liquid Form and Co-Administration of Enteral Nutrition - Serena Logrippo; Roberta Ganzetti; Matteo Sestili; Diego Romano Perinelli; Marco Cespi; Giulia Bonacucina (MDPI AG, 2024)
Background: Compounding solid oral dosage forms into liquid preparations is a common practice for administering drug therapy to patients with swallowing difficulties. This is particularly relevant for those on enteral nutrition, where factors such as the administration procedure and co-administration of enteral nutrition play crucial roles in effective drug delivery. Due to the limited studies focused on this practice, the impact of co-administered nutrition remains unclear. Methods: Pravastatin tablets were compounded into two liquid formulations and administered through three independent tubes for ten cycles. The drug amount was quantified upstream and downstream of the tubes both with and without different (fiber content) nutritional boluses. Results: The compounding procedure did not lower the drug amount with respect to the original tablets. However, when the liquid formulation was pumped through the tubes, a statistically significant reduction in the pravastatin administered (between 4.6% and 11.3%) was observed. The co-administration of different nutritional boluses or the compounding procedure did not affect the general results. Conclusions: Pravastatin loss appears unavoidable when administered via the enteral tube. Although, in this case, the loss was of limited clinical relevance, it is important not to underestimate this phenomenon, especially with drugs having a narrow therapeutic index.